Limiting lumens: a new role for Cdc42 - Lechler, Terry (The Rockefeller University Press, 2008)
The formation of a single lumen is a necessary step in the formation of biological tubes. Different tissues have developed diverse ways to form their lumens. In this issue, Jaffe et al. (Jaffe, A.B., N. Kaji, J. Durgan, and A. Hall. 2008. J. Cell Biol. 183:625–633) report the development of an in vitro system for studying lumen formation that is driven by fluid transport, recapitulating intestinal lumen formation. Effective ion and fluid transport requires both cell polarity and proper tissue organization. Surprisingly, polarization of cells in this three-dimensional system does not require Cdc42. Instead, Cdc42 prevents formation of multiple lumens by orienting cell divisions and directing apical membrane biogenesis.